Development in independent Sri Lanka: what went wrong? - Kelegama, Saman (2000)
Independent Sri Lanka's failure to live up to its initial promise in the area of economic development could be attributed inter alia to: (a) a foreign-exchange crisis which persisted till 1977 because the exigencies of electoral politics bound the country to welfare-oriented, inward-looking policies; and (b) the eruption of conflict between the two main communities as of 1983. - Reproduced
Keywords: Economic and social development - Sri Lanka; Economic and social development